Competency paradigm for educational practice. Fostering key competencies for socio-economic development - Kowalewska, Karolina (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
Socio-economic development rests upon many factors, among which the intangible factors, especially social and human capital, gain in importance. The development of the capital should take place through shaping of a wide range of competencies, with social competencies being those of crucial importance. It seems that in the nearest future, not only a high level of employees’ knowledge and abilities will be the key to functioning of establishments but also proper interpersonal behaviour and attitude. The article thus explains how the competency paradigm contributes to the progression of those abilities that are vital to socioeconomic development.